Understanding the Effects of Low Salinity on Fertilization Success and Early Development in the Sand Dollar Echinarachnius parma. - Pechenik, Jan A.; Allen, Jonathan D. (Tufts University. Tisch Library., 2017)
Free-spawning marine invertebrates that live near shore or in estuaries may experience reduced fertilization success during low-salinity events. Although several studies have documented reproductive failure at reduced salinity in estuarine animals, few have looked at whether developmental failure is due to a failure of fertilization or to a failure of fertilized eggs to cleave. In this study, we examined the effects of salinities ranging from 18 to 32 psu on fertilization success and early development in the sand dollar Echinarachnius parma. In addition to decoupling the effects of low salinity on fertilization from its effects on early cleavage, we also assessed whether eggs or sperm were the weak link in accounting for reproductive failure. We found that both fertilization and cleavage failed at salinities below about 22 psu but that development could be partially rescued by returning zygotes to full-strength seawater. We also found that sperm remained active and capable of fertilizing eggs even after being exposed to low salinities for 30 min.. Taken together, these results suggest that reproductive failure at low salinities in E. parma is due more to an inability of the fertilized eggs to cleave than to an inability of sperm to fertilize eggs.